2015
DOI: 10.1128/jcm.03049-14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Epidemiology of Staphylococcus argenteus Infections in Thailand

Abstract: Molecular typing of 246 Staphylococcus aureus isolates from unselected patients in Thailand showed that 10 (4.1%) were actually Staphylococcus argenteus. Contrary to the suggestion that S. argenteus is less virulent than S. aureus, we demonstrated comparable rates of morbidity, death, and health care-associated infection in patients infected with either of these two species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 16 publications
10
102
1
Order By: Relevance
“…All three isolates carried the common virulence hla , hlb, and clf A. Surprisingly, previous studies have reported that S. argenteus is negative for the pvl (Thaipadungpanit et al., ), but we found the pvl in two S. argenteus isolates in this study. These three S. argenteus isolates, isolated from rabbits, had the ability to cause severe illness in these animals, particularly via the presence of clf A, which usually contributes to abscess formation in rabbits, as previously reported (Malachowa et al., ).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…All three isolates carried the common virulence hla , hlb, and clf A. Surprisingly, previous studies have reported that S. argenteus is negative for the pvl (Thaipadungpanit et al., ), but we found the pvl in two S. argenteus isolates in this study. These three S. argenteus isolates, isolated from rabbits, had the ability to cause severe illness in these animals, particularly via the presence of clf A, which usually contributes to abscess formation in rabbits, as previously reported (Malachowa et al., ).…”
Section: Discussioncontrasting
confidence: 80%
“…Other molecular techniques, such as matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS), nonribosomal peptide synthetase (NRPS) gene amplification, and multilocus sequence type (MLST) determination, were thus recommended in many publications as tools for the identification of S. argenteus (Chantratita et al., ; Schuster et al., ; Zhang et al., ). Some sequencing types of S. aureus were previously confirmed to be S. argenteus , such as ST2793, ST1223, and ST2250 (Chantratita et al., ; Schuster et al., ; Thaipadungpanit et al., ; Tong et al., ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…ST75, ST850, ST883, ST1223, ST1304, ST1850) [2][3][4][5]. Such strains were isolated mainly from indigenous populations in Australia and French Guyana [2,4,6], but also in Cambodia, Fiji, Trinidad and Tobago, Thailand [7][8][9][10] and from animals in Africa [11,12]. No strain harbouring the PVL was described among these isolates, which were considered as having an attenuated virulence compared with other S. aureus strains [5,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Thailand demonstrated that 4.1% of isolates believed to be S. aureus were subsequently determined to be S. argenteus (27). This organism was associated primarily with community-acquired skin and soft tissue infections, although bacteremia and bone and joint infections were seen in three and two patients, respectively (27).…”
Section: Gram-positive Coccimentioning
confidence: 99%